1986
DOI: 10.1002/jlb.39.6.671
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Protein Kinase C and Inhibitor Activity of Protein Kinase C in Rabbit Peritoneal Neutrophils

Abstract: Analysis of the cytosol fraction containing protein kinase C activity from rabbit peritoneal neutrophils by DEAE-cellulose chromatography identified protein kinase C activity in the fractions eluted with 0.08 M-0.14 M NaCl and protein kinase C inhibitor activity in the fraction eluted with 0.16 M-0.5 M NaCl. On further analysis by Sephadex G-150 gel filtration, one peak of protein kinase C and two peaks of inhibitor activity were identified. The peak of protein kinase C and two peaks of inhibitor activity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is not known if PKC-I binds to phosphatidylserine-containing vesicles, but preliminary results (not shown) from our laboratory suggest that PKC-I binding to PKC prevents its association with phosphatidylserine. Second, a soluble PKC inhibitor from rabbit peritoneal neutrophils has a reported molecular mass of 67 kDa [31]. Finally, the low-molecular-mass antibiotic peptides known as defensins HNP-1, HNP-2 and HNP-3 (< 3.5 kDa) all inhibited PKC non-competitively with respect to cofactors, ATP and substrate [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known if PKC-I binds to phosphatidylserine-containing vesicles, but preliminary results (not shown) from our laboratory suggest that PKC-I binding to PKC prevents its association with phosphatidylserine. Second, a soluble PKC inhibitor from rabbit peritoneal neutrophils has a reported molecular mass of 67 kDa [31]. Finally, the low-molecular-mass antibiotic peptides known as defensins HNP-1, HNP-2 and HNP-3 (< 3.5 kDa) all inhibited PKC non-competitively with respect to cofactors, ATP and substrate [21].…”
Section: Discussionmentioning
confidence: 99%
“…We [29] and others [30][31][32] have previously described endogenous inhibitors of PKC which may modulate PKC activity and thereby certain cellular functional events in vivo. The neutrophil PKC inhibitor, PKC-I, is heat-and proteinasesensitive, is not itself a proteinase, and appears to be present primarily in the membrane fraction of specific granules and in the plasma-membrane fraction [29].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that PKC activity in cytosolic preparations of the ovary of the pseudopregnant and pregnant rat is masked by an endogenous inhibitor of PKC [6][7][8], and we have recently demonstrated that this PKC-inhibitory factor in the rat ovary is a protein phosphatase [9]. Endogenous inhibitors have been identified in other tissues [10][11][12][13][14][15][16]. To date, only one of these has been shown to be a protein phosphatase [16].…”
Section: Introductionmentioning
confidence: 98%